Genome-wide identification and characterization of NCED gene family in soybean (Glycine max L.) and their expression profiles in response to various abiotic stress treatments - Md Shohel Ul Islam; Pollob Shing; Mahin Ahmed; Fatema Tuz Zohra; Amina Rownaq; Suronjeet Kumar Paul; Shaikh Mizanur Rahman; Md. Abdur Rauf Sarkar (PLoS ONE, 2025)
The NCED (9-cis-epoxy carotenoid dioxygenase) enzyme regulates the biosynthesis of abscisic acid (ABA), which is responsible for plant growth, development, and response to various environmental challenges. However, no genome-wide identification, characterization, functional regulatory element analysis, and expression profiles in response to different abiotic stresses of the NCED gene family have yet to be investigated in an economically important legume plant species, soybean (Glycine max L.). Through comprehensive analysis, 16 NCED genes (named GmNCED1 to GmNCED16) belonging to the RPE65 domain were identified in the soybean genome and found to be unequally distributed over 9 distinct chromosomes. The distinct intron-exon structures of GmNCED genes were categorized into six groups and shared a close relationship with the grapevine. Segmental gene duplication events and the purifying selection process were evident in GmNCED genes, according to evolutionary studies. Cis-acting regulatory element analysis revealed that GmNCED genes were largely associated with light response as well as stress response. ERF, MYB, bZIP, and LBD emerged as the major transcription factors in GmNCED genes. The protein-protein interactions demonstrated the close relationship between GmNCED and Arabidopsis thaliana proteins, while micro-RNA analysis revealed the involvement of GmNCED genes in plant growth and development as well as in the regulation of abiotic stress. The expression profiles of GmNCED2, GmNCED11, and GmNCED12 provided evidence of their engagement in dehydration and sodium salt stress, whereas GmNCED14 and GmNCED15 were up-regulated in drought stress. Moreover, the up-regulation of GmNCED13 and GmNCED14 genes in heat tolerant germinated seed stages at high temperature delta region. More specifically, GmNCED14 might be used as a novel candidate gene under drought stress, and influencing seed germination at high temperature. Overall, this study identified the crucial role of GmNCED in conferring resistance against abiotic stress such as dehydration, salt, and drought, and also uncovering the detailed regulatory mechanism of ABA biosynthesis during seed germination.